CD38‐NADase is a new major contributor to Duchenne muscular dystrophic phenotype - Antoine de Zélicourt; Abdallah Fayssoil; Mbarka Dakouane‐Giudicelli; Isley De Jesus; Ahmed Karoui; Faouzi Zarrouki; Florence Lefebvre; Arnaud Mansart; Jean‐Marie Launay; Jerome Piquereau; Mariana G Tarragó; Marcel Bonay; et al. (EMBO Molecular Medicine)
Abstract Duchenne muscular dystrophy (DMD) is characterized by progressive muscle degeneration. Two important deleterious features are a Ca2+ dysregulation linked to Ca2+ influxes associated with ryanodine receptor hyperactivation, and a muscular nicotinamide adenine dinucleotide (NAD+) deficit. Here, we identified that deletion in mdx mice of CD38, a NAD+ glycohydrolase‐producing modulators of Ca2+ signaling, led to a fully restored heart function and structure, with skeletal muscle performance improvements, associated with a reduction in inflammation and senescence markers. Muscle NAD+ levels were also fully restored, while the levels of the two main products of CD38, nicotinamide and ADP‐ribose, were reduced, in heart, diaphragm, and limb. In cardiomyocytes from mdx/CD38−/− mice, the pathological spontaneous Ca2+ activity was reduced, as well as in myotubes from DMD patients treated with isatuximab (SARCLISA®) a monoclonal anti‐CD38 antibody. Finally, treatment of mdx and utrophin–dystrophin‐deficient (mdx/utr−/−) mice with CD38 inhibitors resulted in improved skeletal muscle performances. Thus, we demonstrate that CD38 actively contributes to DMD physiopathology. We propose that a selective anti‐CD38 therapeutic intervention could be highly relevant to develop for DMD patients.